AN ANALYSIS OF TRANSLATION TECHNIQUE IN DEAR JOHN NOVEL BY NICHOLAS SPARKS - Julaeha, Siti (Faculty of Social and Political Sciences University of Bangka Belitung, 2023)
This research aims to analyze the use of translation techniques contained in the letters to the novel Dear John by Nicholas Sparks. The research method used is text analysis with a qualitative approach. Data is collected with observation techniques, library studies, and document analysis. The analysis and interpretation of the research data were carried out and studied by following the six steps of the qualitative data analysis techniques adopted by Creswell (2009) through the comparison analysis between the original text in English and the translation in Indonesian, with a focus on the selection of appropriate matches to express the correspondence, language style, and meaning of the letters. The results of the study showed that the translators used seven translation techniques out of 18 developed by Molina and Albir (2002), namely using literal techniques at 35.3%, Transposition techniques at 17.7%, generalization, amplification, and adaptation techniques at 11.8%, and modulation and borrowing techniques at 5.8%. The most commonly used technique is the literal technique.